Effectiveness Test of Indigenous Plant Growth Promoting Rhizobacteria (PGPR) Isolate on the Growth of Acehnese Patchouli (Pogostemon cablin Benth.) Sidikalang Variety - Halimursyadah, Halimursyadah; Fidia, Yayang; Husna, Rika (Jenderal Soedirman University, 2024)
Plant Growth Promoting Rhizobacteria (PGPR) is a group of bacteria that live saprophytically in the root area (rhizosphere) acting as a plant growth promoter. The purpose of this study was to test the effectiveness of indigenous rhizobacterial isolates from Aceh Besar and Aceh Tengah in supporting the growth of Aceh patchouli Sidikalang variety. This research was conducted at the Laboratory of Seed Science and Technology, Faculty of Agriculture, Syiah Kuala University and patchouli planting was carried out at the Patchouli Innovation Park (Nino Park), Syiah Kuala University, which took place from December 2022 to June 2023. This study used a non-factorial Randomized Group Design (RAK) with 3 replications. The factor studied was the type of rhizobacterial isolate consisting of 15 treatment levels, namely 1 treatment without rhizobacteria, 7 treatments given indigenous rhizobacterial isolates from Lambada, Seulimeum District, Aceh Besar Regency and 7 treatments given rhizobacterial isolates from Paya Tampu village, Rusip Antara District, Central Aceh Regency. The observation parameters studied are of plant height, number of leaves, number of branches, stem diameter, area per leaf blade, root length, root volume and wet biomass weight of plants. The results showed that indigenous rhizobacterial isolates from Aceh Besar and Aceh Tengah effectively increased the average plant height of Sidikalang variety patchouli at 4 and 8 MSA (26%, and 24%), number of leaves (46%, and 58%), number of branches (78% and 50%), area per leaf blade (34%), root length (19%), root volume (60%) and plant wet biomass weight (50.61%).